Northwest History. Alaska. Earthquakes & Volcanoes. (1933)
Alaskan Quake Forced Men To Hold On Trees. ALASKAN QUAKE FORCED MEN TO HOLD ON TREES ANCHORAGE, Alaska, May 9. (/P) —Temblors so violent that men had to hold on to trees to keep their feet were described here today by George Carter and Bob Weimer of Anchorage who were trapping on the wide flats of the east side of the Susitna river at the time of the earthquake of April 26. They were at the mouth of the river where it joins Cook inlet, and arrived here yesterday In a small launch. The trappers said the quake struck with such force that huge cracks, some five feet wide at the top, appeared on the surface of the earth, running mostly parallel to the river, but some breaking irregularly in the opposite direction. When the gashes began to close, they said, mud spurted 20 feet high. At first they could see far down into the cracks, but with rising tides they filled. The surface formation in the area affected is chiefly of river deposit, covered with tundra grass, and similar to swampland. Five Miles in Extent. Carter and Weimer said the scene was as if some one had split the earth with a huge cleaver. The section hit is about 20 to 25 miles west of here, and the ruptures were over an area about five miles square. Thousands of dead trees fell when the earth shook; log cabins were torn apart, and ice along the river and lake shores, which was about five feet thick, cracked into huge pieces and were shoved upon the shore. The next most violent disturbance was reported from Tyonek, where roofs shifted several feet on large buildings, and at Curry on the Alaska railroad, where the quakes were about the same as felt here. These were much less than those at the mouth of the Susitna. Light tremors are still beging felt in this region once' or twice daily.